Green‐, Red‐, and Infrared‐Emitting Polymorphs of Sterically Hindered Push–Pull Substituted Stilbenes. Issue 13 (30th December 2020) - Pauk, Karel; Luňák, Stanislav; Růžička, Aleš; Marková, Aneta; Mausová, Anna; Kratochvíl, Matouš; Melánová, Klára; Weiter, Martin; Imramovský, Aleš; Vala, Martin
Abstract: The synthesis, XRD single‐crystal structure, powder XRD, and solid‐state fluorescence of two new DPA‐DPS‐EWG derivatives (DPA=diphenylamino, DPS=2, 5‐diphenyl‐stilbene, EWG=electron‐withdrawing group, that is, carbaldehyde or dicyanovinylene, DCV) are described. Absorption and fluorescence maxima in solvents of various polarity show bathochromic shifts with respect to the parent DPA‐stilbene‐EWGs. The electronic coupling in dimers and potential twist elasticity of monomers were studied by density functional theory. Both polymorphs of the CHO derivative emit green fluorescence (527 and 550 nm) of moderate intensity (10 % and 5 %) in polycrystalline powder form. Moderate (5 %) red (672 nm) monomer‐like emission was also observed for the first polymorph of the DCV derivative, whereas more intense (32 %) infrared (733 nm) emission of the second polymorph was ascribed to the excimer fluorescence. Abstract : Intense near infrared shining : Push–pull substituted stilbenes, decorated with a pair of side phenyls, form solid‐state emitting polymorphs. Parallel offset face‐to‐face packing of the side phenyls enable the formation of crystals consisting of the electronically coupled isolated dimers, showing rare excimer type intense emission in the near infrared region.